2020
DOI: 10.14499/indonesianjcanchemoprev11iss1pp30-35
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, Anti-Inflammatory and Anti-Biofilm-Forming Activity of Potato (Solanum tuberosum L.) Peel Extract

Abstract: The utilization of natural resources, one of which is plants, has been researched as an alternative to synthetic drugs because of their natural content. Potato (Solanum tuberosum L.) peels, the parts of potatoes that are often cut off and discarded, have been reported to have some phenolic compounds and flavonoids in their composition. The extract of potato peels was investigated for its analgesic, anti-inflammatory, and anti-biofilm-forming properties. A hot plate test was conducted to assess the analgesic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Doses for RSA 40 µL and 0.1 µL for FRAP 3 Wahyudi et al, 2020. 18 Indonesia Analgesic, anti- inflammatory, and anti-biofilm-forming activity in potato peel extract Solanum tuberosum Potato peel ethanol extract Phenol and flavonoid compounds Yes (anti-inflammatory activity) No (anti-biofilm activity) Analgesic activity with Wistar rats by placing at hotplate 60°C, anti- inflammatory activity with Wistar rats induced by 1% carrageenan, anti-biofilm activity with streptococcus ATCC 25175. Significant as anti- inflammatory, anti-biofilm, and analgesic Analgesic uses 50, 100 and 200 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Doses for RSA 40 µL and 0.1 µL for FRAP 3 Wahyudi et al, 2020. 18 Indonesia Analgesic, anti- inflammatory, and anti-biofilm-forming activity in potato peel extract Solanum tuberosum Potato peel ethanol extract Phenol and flavonoid compounds Yes (anti-inflammatory activity) No (anti-biofilm activity) Analgesic activity with Wistar rats by placing at hotplate 60°C, anti- inflammatory activity with Wistar rats induced by 1% carrageenan, anti-biofilm activity with streptococcus ATCC 25175. Significant as anti- inflammatory, anti-biofilm, and analgesic Analgesic uses 50, 100 and 200 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“… 16 Flavonoids, as reported in the research, exhibit antioxidant, anticarcinogenic, antibacterial, anti-inflammatory, anti-allergic, analgesic , and antiviral properties. 12 , 18 Flavonoids act as antioxidants by neutralizing reactive oxygen species (ROS) . Free radicals suppress the level of antioxidants, which leads to oxidative instability, known as oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 S. tuberosum is an important source of phenolic compounds such as chlorogenic acid and gallic acid, besides, it has flavonoids principally in its peel, these phytoconstituents exert antioxidant, analgesic, antiinflammatory activities. [16][17][18][19][20] S. tuberosum "potato" is used in the elaboration of food products, medicines, and packaging. Likewise, it has recently been found that pigmented potatoes that contain high concentrations of anthocyanins and carotenoids could have potential medicinal utility.…”
Section: Introductionmentioning
confidence: 99%